Chronic appendicitis in an atrophic appendix: Case report - Trujillo L., Yeray (2016)
Chronic appendicitis is a rare entity characterized by pain in the right iliac Fossa during 2 years of evolution. Some surgeons and pathologists deny the existence of this disease; in contrast, there are studies of different authors that reported findings of chronic appendicitis. Male patient, 71 years- old, with pain in the right iliac Fossa of 2 weeks of evolution which remitted partially throughout his presentation, not associated with nausea, vomiting or anorexia. Physical examination revealed bounce in right iliac Fossa and blood count without Leukocytosis and forms segmented within normal parameters. History of 2 years of similar symptoms with resolution spontaneously. It was decided to carry out exploratory laparotomy; the operative finding was a cecal appendix of 1 cm of length with adherence of its distal part to the abdominal wall, exerting traction. Postoperatively the patient presented mild bloating and complete remission of pain. The pathological anatomy of the operative part was informed as cecal appendix 1 cm of length with chronic inflammation and fibrosis.